(untitled) (Raparin Journal of Humanities (RJH), 2021)
Nostalgia for the past is a phenomenon that is present in most members of society, but its impact varies from one person to another, and nostalgia appears in humans in cases of distance and alienation from the homeland, in other words when a person is uprooted from his roots and spends his life in the diaspora, and here nostalgia for the past dominates his thinking and reflections . And nostalgia leaves a deep impact on the author. That is why the book resorts to the world of writing to get rid of the pain of alienation. And back again to the world of childhood. With this hope, they can interrupt for a moment from the present time and return to the time of youth. Here, they can make a magical trip to the past in order to give their souls and themselves a moment of calm and stability. In this research, we have tried to embody the types of nostalgia in the novel (ALWAN and AFSANE).